Combined Carotid Endarterectomy and Coronary Artery Bypass Grafting : Review - Alam, SAN (Cardiovascular Journal, 2011)
Considerable progress has been made over the last 2 decades in diagnosing and treating patient with ischaemic heart and atherosclerotic carotid diseases. Next to operative mortality, an irreversible perioperative cerebrovacular accident is the most dreaded perioperative complication of myocardial revacularisation; primarily because of the devastating consequences to the patient and because of the significantly increased cost of hospitalization and post hospital care. Perioperative stroke following coronary artery bypass grafting increasingly concerns the cardiac surgeon, because the average age of coronary bypass patients continues to rise and with it the risk of stroke. This article will elaborate the relationship of carotid artery disease to perioperative neurologic complications following myocardial revacularisation, evaluate treatment options and provide guidelines on optimum patient selection and timing for each intervention either isolated or in combination. Key words: CABG, Carotid artery stenosis, Carotid endarterectomy DOI: http://dx.doi.org/10.3329/cardio.v1i1.8210 Cardiovasc. j. 2008; 1(1) : 59-63